Analisis Perilaku Kekuatan Kolom Semi Pracetak Akibat Beban Aksial Dan Beban Lateral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Semi-precast column uses the combination of cast-in-place concrete and precast concrete. In semi-precast concrete column, difference in compressive strength exists between the cast-in-place and precast concrete. This research aims to investigate the behaviour of semi-precast concrete column by varying the compressive strength of the precast concrete.The semi-precast concrete columns were modeled in finite element analysis software as the connection between column and fondation models. The height of the column models were half of the real columnâs height, based on the consideration that the elastic inflection point occurs at half the columnâs height. For all column models, the compressive strength of the cast-in-place concrete was 20 MPa. However variations were made for the compressive strength of the precast concrete component: 8 MPa, 12 MPa, 16 MPa, and 20 MPa. The column models were given constant axial loads and inclined lateral loads. The outputs of the finite element analysis software were lateral load-deflection relationship and crack pattern. Based on the analysis results, the magnitude of the lateral load and deflection of the column were proportional to the increment of concrete compressive strength. The cracks that occur at all semi-precast concrete column model were flexural cracks at points with highest bending moment. It could also be observed that the crack pattern was parallel with the stirrups at tension fiber of the column.Keywords: Column, semi-precast, cast-in-place, finite element analysis software